The occurence of polyprenols in Euphorbiaceae - George Verughese; Murughan Muthukrishnan; Tadeusz Chojnacki (Acta Societatis Botanicorum Poloniae, 2014)
The distribution and occurrence of polyprenols in leaves of 19 species belonging to the Euphorbiaceae family were investigated. Polyprenols comprising 11 and 12 isoprene units were the dominant ones in the majority of the plants investigated. Out of the 19 species studied the highest concentration of polyprenols was observed in Phyllanthus amarus (0.1-0.3%, dry wt.).